WBAN Mitigation method: Comparison of Diversity Techniques in fading - Sindhu, Savita; Vashisth, Dr. Shruti (British Journal of Healthcare and Medical Research, 2017)
In WBAN various sensors and actuators are connected together either on the body, under the skin of person or on the clothes of the person. This network expands when the signals from the body are picked and sent over a wireless channel. The world that we live in has become very advanced, and hence it is required that the technology we use for communicating the signal should be very expeditious, i.e. our data carrying signals should profuse in excellently, so that data can be communicated without any intervention as the signals picked from body are of short range. But the data carrying signals that are relayed from one place to other often encounter various interferences in their path. One of the major problems in communicating wirelessly that has to be dealt with is fading. In WBAN if the signals can be captured with maximum information we can easily diagnose patient's disease for example; Cardiovascular diseases, diabetes control etc.Diversity is an important aspect that helps in dealing with the effects of fading. This paper focuses on the diversity techniques which is one of the popular mitigation methods; in different fading channels in WBAN. It also provides a comparative study of diversity techniques in fading channels with respect to AWGN channel.